Electrically detected electron nuclear double resonance in amorphous hydrogenated boron thin films - Myers, Kenneth J.; Manning, Brian; Lenahan, Patrick M. (Solid state communications, 2022)
We report on electrically detected electron nuclear double resonance (EDENDOR) observations via spin dependent trap assisted tunneling (SDTAT) in amorphous boron thin films at 250 K. We observe EDENDOR from both 10B and 11B nuclei, likely interacting with carbon impurities. In SDTAT, electron paramagnetic resonance (EPR) is detected through a change in the trap assisted tunneling current through the thin film. As in conventional electron nuclear double resonance (ENDOR) the ENDOR response is detected through a modest change in the EPR response. Since SDTAT detection sensitivity is about seven orders of magnitude greater than that of conventional EPR, it, in principle, can provide an enormous boost in ENDOR sensitivity. This enormous potential sensitivity improvement can be compromised by a coupling of the RF electromagnetic field driving the nuclear spin response and the electrical leads which are utilized to monitor the resonance induced changes in device current. We overcome this difficulty with the introduction of proportional-integral-derivative (PID) control of the RF circuitry which greatly suppresses fluctuations in the amplitude of the RF magnetic field at the thin film structure under investigation. •Electrical detection of 10B and 11B nuclei via electron nuclear double resonance.•Electrically detected electron nuclear double resonance in a complex spin system.•Proportional-integral-derivative controller for nuclear frequency power smoothing.